Early Neolithic diets at Baijia, Wei River valley, China: stable carbon and nitrogen isotope analysis of human and faunal remains - Grice, Kliti; Atahan, P.; Li, X.; Chen L.; Hu, S.; Zhou, X.; Burtuch, F. (Academic Press, 2011)
Stable carbon and nitrogen isotope values are presented for faunal and human bone collagen from Baijia, in the Wei River valley region of Shaanxi Province, China. The remains have a calibrated age range of ca. 5709–5389 BC, and correspond with the early Neolithic Laoguantai Period. Stable isotopic results indicate that human diets included millet and probably aquatic foods such as fish and shellfish. Bovid samples are tentatively identified as water buffalo, and have a mean δ13C value of -14.6‰, which reflects some millet consumption. Whether bovids were grazing on wild millet, or had diets directly influenced by humans, is not known. The single Sus sample from Baijia had a diet dominated by C3 plants and is thus unlikely to have been a domesticated animal. Overall, the stable isotope results presented here conform to the current concept that the people of the Laoguantai culture were millet farmers, who had subsistence strategies that included hunted wild foods.